Accelerated aging in the tumor microenvironment: Connecting aging, inflammation and cancer metabolism with personalized medicine - Lisanti, Michael P (Landes Bioscience, 2011)
Cancer is thought to be a disease associated with aging. Interestingly, normal aging is driven by the production of ROS and mitochondrial oxidative stress, resulting in the cumulative accumulation of DNA damage. Here, we discuss how ROS signaling, NFκB- and HIF1-activation in the tumor micro-environment induces a form of “accelerated aging,” which leads to stromal inflammation and changes in cancer cell metabolism. Thus, we present a unified model where aging (ROS), inflammation (NFκB) and cancer metabolism (HIF1), act as co-conspirators to drive autophagy (“self-eating”) in the tumor stroma. Then, autophagy in the tumor stroma provides high-energy “fuel” and the necessary chemical building blocks, for accelerated tumor growth and metastasis. Stromal ROS production acts as a “mutagenic motor” and allows cancer cells to buffer—at a distance—exactly how much of a mutagenic stimulus they receive, further driving tumor cell selection and evolution. Surviving cancer cells would be selected for the ability to induce ROS more effectively in stromal fibroblasts, so they could extract more nutrients from the stroma via autophagy. If lethal cancer is a disease of “accelerated host aging” in the tumor stroma, then cancer patients may benefit from therapy with powerful antioxidants. Antioxidant therapy should block the resulting DNA damage, and halt autophagy in the tumor stroma, effectively “cutting off the fuel supply” for cancer cells. These findings have important new implications for personalized cancer medicine, as they link aging, inflammation and cancer metabolism with novel strategies for more effective cancer diagnostics and therapeutics.